Impact of the COVID-19 Pandemic on Delay in Treatment Initiation for Oral Cavity and Oropharyngeal Cancer in Brazil - Israel Monteiro Araújo; Márcio Vinícius Campos Borges; Luís Gustavo Souza Santos; Jessilene Ribeiro Rocha; Érika Martins Pereira; Vandilson Pinheiro Rodrigues (Association of Support to Oral Health Research (APESB), 2024)
Objective: To analyze the impact of the COVID-19 pandemic on the interval between diagnosis and initiation of treatment for oral cavity and oropharyngeal cancer in Brazil. Material and Methods: A time series study was conducted using secondary data extracted from the DATASUS system. The three-year period from 2019 to 2021 was selected to represent the baseline, onset, and peak of reported COVID-19 cases. The dependent variable of the study was the delay in starting anticancer treatment (>60 days after histopathologic diagnosis). Time series were analyzed using joint-point regression and monthly percentage changes (MPC) were estimated. Results: For oral cavity cancer, there were two periods of decrease in the delay in treatment initiation, from January 2019 to June 2020 (MPC= -0.75, 95% CI = -0.3 to -3.2, p=0.004) and from November 2020 to December 2021 (MPC= -1.41, 95% CI = -2.2 to -0.6, p=0.001). For oropharyngeal cancer, there was an increase in the percentage of delays in treatment initiation from January 2019 to February 2020 (MPC= 0.86, 95% CI = 0.2 to 1.5, p=0.014) and from May 2020 to December 2020 (MPC= 3.66, 95% CI = 1.2 to 6.2, p=0.005), with a decrease from December 2020 to December 2021 (MPC= -1.40, 95% CI = -2.3 to -0.5, p=0.003). Conclusion: The COVID-19 pandemic in Brazil had a greater impact on treatment initiation delay for oropharyngeal cancer than for oral cavity cancer. However, the percentage of delay in treatment initiation for oropharyngeal cancer showed fluctuation, with an increase in the pre-pandemic period and a decrease after December 2020.